Anonymous group key distribution scheme for the internet of vehicles - Zhiwang HE; Huaqun WANG (网络与信息安全学报)
Vehicular ad hoc networks (VANET) play a crucial role in intelligent transportation systems by providing driving information and services such as collision prevention and improved traffic efficiency.However, when a trusted third party (TTP) interacts with a vehicle in VANET, it can be vulnerable to security threats like eavesdropping, tampering, and forgery.Many existing schemes rely heavily on TTP for key negotiation to establish session keys and ensure session security.However, this over-reliance on TTP can introduce a single point of failure and redundancy issues when TTP sends the same information to multiple vehicles.Additionally, key negotiation methods used for creating group session keys often result in increased interaction data and interaction times.An anonymous group key distribution scheme for the internet of vehicles was proposed to address these challenges.The Road Side Units (RSUs) were used to facilitate the creation of group session keys among multiple vehicles.Identity-based public key cryptography and an improved multi-receiver encryption scheme were utilized for communication between RSUs and vehicles, enabling two-way authentication and secure distribution of group session keys.During the key distribution process, a single encryption operation was sufficient to allow all group members to obtain a consistent session key.This reduced the reliance on TTP for authentication and group communication.Formal security proofs demonstrate that the proposed scheme satisfies basic security requirements.Furthermore, performance analysis and comparisons indicate that this scheme offers lower computational overhead and communication overhead compared to similar schemes.